Pengaruh Media Proses Pencernaan Berbantuan Augmented Reality Terhadap Hasil Belajar Siswa - Astutik, Leny Suryaning; Ana, Ria Fajrin Rizky; Ulum, Bachrul; Dwinata, Anggara (Jurnal Pendidikan Dasar dan Keguruan, 2024)
Elementary school students are required to learn about the digestive system. Direct observation is challenging because the human digestive system is inside the body. The latest advance in technology that allows simultaneous 2D and 3D visualization is augmented reality. This investigating aims to discover how augmented reality-assisted media influences student learning outcomes, especially on material about the digestive system. This investigating uses an experimental design with quantitative methodology. A quasi-experimental investigating design was adopted. The investigating population was all fifth-grade students at SDN 6 Ngunut. The investigating sample was class V students. Multiple choice objective tests, as well as non-test instruments such as questionnaires, interviews, and documentation, were used in this investigating.The hypothesis test used a paired sample t-test, and the results showed that the count was 8.013, t-table dk = 30-1 = 29, and the significance level (????) = 0.05 was 1.660. Hypothesis test findings show that the t-hitung> t-table (8.013 > 1.660). The result is that H0 is rejected, and H1 is accepted. Thus, it can be said that using media related to the human digestive system, activated by augmented reality, significantly impacts student learning outcomes